2020
DOI: 10.1186/s12964-020-00656-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neurons from dorsal root ganglia regulate endothelial cell function in extracellular matrix remodelling

Abstract: Background Recent physiological and experimental data highlight the role of the sensory nervous system in bone repair, but its precise role on angiogenesis in a bone regeneration context is still unknown. Our previous work demonstrated that sensory neurons (SNs) induce the osteoblastic differentiation of mesenchymal stem cells, but the influence of SNs on endothelial cells (ECs) was not studied. Methods Here, in order to study in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 88 publications
(101 reference statements)
0
23
0
Order By: Relevance
“…[1] Blood vessels can transport oxygen, nutrients, and growth factors to fibroblasts and keratinocytes, and nerve fibers can discriminate pain, temperature, and regulate skin metabolism. [2] However, skin, as the surface of human body, is very easily burned DOI: 10.1002/adhm.202102359 by fires, hot liquids, and chemical products in our daily life. Severe burns can not only destroy the dermal matrix but also damage the cutaneous neurovascular networks, which are difficult to heal by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Blood vessels can transport oxygen, nutrients, and growth factors to fibroblasts and keratinocytes, and nerve fibers can discriminate pain, temperature, and regulate skin metabolism. [2] However, skin, as the surface of human body, is very easily burned DOI: 10.1002/adhm.202102359 by fires, hot liquids, and chemical products in our daily life. Severe burns can not only destroy the dermal matrix but also damage the cutaneous neurovascular networks, which are difficult to heal by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…41 In fact, the observation of molecular mechanisms regulating cellular communication of sensory neurons with EC has further demonstrated that MMP2 and MMP9 protein concentration and enzymatic activity are upregulated when ECs are co-cultured with sensory neurons. 42 This heightens the interconnectivity of angiogenesis and neurogenesis; neural and vascular cultures together play a role in inducing ECM remodeling in response to injury, which allows for cell migration. Recently, we have demonstrated that EC exhibit high MMP activity, and it is well established that the angiogenic factor FGF can stimulate EC MMP production.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments in which sensory neurons (SNs) were co-cultured with endothelial cells, Leroux et al. found that CGRP and SP up-regulated angiogenic markers, including VEGF, angiopoietin 1, and Col4, and promoted angiogenesis ( 66 ). SP can promote angiogenesis, but whether it can target H-type blood vessels to affect bone metabolism still needs further research directions.…”
Section: Peripheral Nerves Innervating Bones and Their Characteristicsmentioning
confidence: 99%
“…Um et al (65) reported that the number of circulating endothelial progenitor cells and CD31+ cells in peripheral blood increased after subcutaneous injection of SP, while CD31+ cells were associated with an angiogenic activity. In experiments in which sensory neurons (SNs) were co-cultured with endothelial cells, Leroux et al found that CGRP and SP up-regulated angiogenic markers, including VEGF, angiopoietin 1, and Col4, and promoted angiogenesis (66). SP can promote angiogenesis, but whether it can target H-type blood vessels to affect bone metabolism still needs further research directions.…”
Section: Sp Regulates Angiogenesismentioning
confidence: 99%